Design criteria of biofilter system as treatment for domestic wastewater - Afiq Aiman, Mohamad Razak (2010)
Nowadays, the effluent from domestic wastewater is highly untreated. So when the effluents flow to the river it will cause water pollution and will affect water quality of the river. If the water polluted, the aquatic life and environment surrounding will be in deep trouble. A device known as biofilter can help this problem solve. To make this biofilter effective, it will depend on the design. The optimum design criteria will make this biofilter become more effective although in the market nowadays have many biofilter but the available biofilter now is doesn't have proper design criteria. This study aims to determine the design criteria of biofilter as treatment for domestic wastewater and to evaluate the effectiveness of biofilter as treatment for domestic wastewater. This study involves two main methods which are field measurement and laboratory experiments. Field measurement includes test for Dissolved Oxygen (DO), Total Dissolved Solid (TDS), pH, temperature, salinity, turbidity and electric conductivity while laboratory experiments involve test for Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Ammonia Nitrogen (AN), Total Coliform, E-Coli and Oil and Grease. All the results were compare with Standard A and Standard B, Environment Quality Act, 1974 and analyzed in terms of percentages of removal. The study indicates that the design criteria adopted not shows an excellent performance where most of the water quality parameters not complying Standard A and Standard B, Environment Quality Act, 1974, however it do shows improvement in terms of percentage of removal for parameters turbidity, total suspended solid and ammonia nitrogen The percentage removal of turbidity as high as 98.99%, while TSS and AN range from 31.25% to 58.55%.